LEVEL OF EXTENSION METHODS IMPORTANCE FROM THE AGRICULTURAL EXTENSION WORKERS POINT OF VIEW IN SULAIMANI GOVERNORATE - Dlger Salih M. Mohammad; Mohammed Omer Mohammed Sakina (University of Thi-Qar Journal of agricultural research, 2023)
The aim of this study was to determine the level of agricultural extension methods importance from the extension workers point of view in Sulaimani governorate, then identify relationship between agricultural extension methods importance with some variables. The population consists of the all agricultural extension workers in agricultural extension directorate of Sulaimani and they were (137) workers, the sample of the research included (106) respondents representing nearly (%77) of the population, taken by a simple sampling random method. Questionnaire was prepared to collect the data. The results showed that the level of importance of extension methods were high tends to medium, group extension methods occupied the first rank in the level of importance of extension methods. Farm visit paragraph occupied the first rank in the individual method, then field demonstration paragraph occupied the first rank in the group method finally extension campaigns paragraph occupied the first rank in the mass method. The results also showed there is a significant relationship between the level of importance and each of the following variables (Previous training, Exposure to sources of the agricultural information. Attitude towards agricultural extension. Job satisfaction). While not significant relationship between the level of importance of extension methods and the other variables. The researchers recommended pay attention to energizing their programs through agricultural extension methods, and Focusing on activating the group method, Agricultural extension department should pay attention for the workers to participate in training courses.